Mechanisms of clay mineral-induced targeted deposition and synergistic CO2 sequestration potential in the CCUS-EOR process - Miaoxin Zhang; Jingchun Wu; Liyuan Cai; Bo Li; Yang Zhao; Yangyang Hou; Fang Shi; Chunlong Zhang (PLoS ONE, 2025)
Background Strongly water-sensitive reservoirs with high clay content face challenges in conventional development due to clay swelling and impeded seepage. CO2 injection shows potential for enhanced oil recovery (EOR) and carbon sequestration; however, the role of clay minerals in regulating CO2-induced asphaltene deposition and sequestration remains unclear. Methodology We conducted experiments on clay-oil interactions, nuclear magnetic resonance (NMR), measurements of crude oil properties, and long core water flooding tests to evaluate deposition, reservoir damage, and CO2 sequestration. Conclusions/Significance Results demonstrate that clay minerals significantly promote CO2-induced asphaltene deposition, with the deposition amount in clay-containing crude oil increasing by 37% compared to clay-free systems. The interfacial tension (IFT) between crude oil and CO2 decreases from 15.68 to 12.53 mN/m at 10 MPa with increasing clay content, while crude oil viscosity reduces by up to 43.58% when CO2 injection exceeds 30 mol%. Microscale NMR analysis confirms that clay-asphaltene aggregates preferentially block large pores, reducing reservoir heterogeneity and enhancing CO2 sequestration in medium/small pores. Macroscale long-core experiments highlight the significance of high clay mineral content for geological sequestration, showing that the CO2 sequestration rate increases from 43.15% to 48.21% as clay content rises from 8.35% to 29.92%. Although deposition slightly impairs permeability, it drives CO2 into medium/small pores, thereby achieving a balance between oil recovery efficiency and long-term storage stability.